2012
DOI: 10.1016/j.enbuild.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shading control patterns on the energy assessment of office spaces

Abstract: a b s t r a c tThis work reviews existing models of control patterns for occupant-shading interactions in office buildings, and studies their influence in terms of energy demand when comparing transparent faç ade alternatives. It starts by establishing a review of visual comfort criteria in office buildings and of the conditions that prompt occupants to interact with shading devices and electric lighting. Given the large variety of parameters identified as primary variables in the existing literature -hence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 36 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…Existing studies (Dubois and Blomsterberg 2011;Silva et al 2012) have found that control strategies are not without flaws, making for higher real energy consumption than simulations have predicted. The sensitivity analysis performed in this work sheds light on how to better accommodate user behaviour in the design of shading control strategies and how to make the control strategies more robust, focusing on a cold climate.…”
Section: The Task At Handmentioning
confidence: 99%
“…Existing studies (Dubois and Blomsterberg 2011;Silva et al 2012) have found that control strategies are not without flaws, making for higher real energy consumption than simulations have predicted. The sensitivity analysis performed in this work sheds light on how to better accommodate user behaviour in the design of shading control strategies and how to make the control strategies more robust, focusing on a cold climate.…”
Section: The Task At Handmentioning
confidence: 99%
“…Previous studies have proposed various methods to reflect the movement of a shading device in an annual energy calculation [2,11,12,24,25]. The capability of accurately describing the movements and the positions of a shading device in these studies, however, was limited because they either divided the operation steps simply into "open" or "close", or they provided limited number of shading types of which the operation steps can bet set.…”
Section: Setting Shading Positionsmentioning
confidence: 99%
“…In the case of solar radiation reaching the façade exceeding a certain range, researchers have looked into a method of controlling solar heat gain by closing the shading device [2,24,27]. With respect to natural lighting, in the case of the illuminance on the indoor working plane of less than or equal to 1800 lux or 2000 lux, studies have been conducted to determine a control method to maintain an effective illuminance indoors [2,11]. To compare the annual primary energy according to the control strategies of an external movable shading device, three control strategies were selected on the basis of conventional studies related to solar radiation heat and natural lighting.…”
Section: Description Of Different Shading Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are placed on the roof, exterior façade, next to the windows, or inside windows surfaces to measure global solar radiation. Subsequently, shading control algorithms using the value of solar radiation to operate shading systems adjust the tilt angle of the venetian blinds [32,33], opening or closing of shutters and blinds [31,[34][35][36]. Several studies of shading control algorithms based on solar radiation measurements have shown great potential for energy savings [20,30,32,37,38].…”
Section: Introductionmentioning
confidence: 99%